The effect of nerve mobilization exercise in patients with rheumatoid arthritis: a pilot study - C.-N. Lo; G. Xia; B.P. Leung (PAGEPress Publications, 2017)
Rheumatoid arthritis (RA) is an autoimmune disorder characterized by chronic inflammation of the joints. The neurogenic inflammatory mechanism plays an important role in the inflammatory process of RA, and pathological changes in neural tissues in RA have also been noted. We aim to investigate treatment of the nervous system to relieve joint pain and inflammation in RA. Nerve mobilization, a nervous system-specific therapeutic exercise, was applied on RA patients to determine the effect of nerve mobilization on joint inflammation. Twelve RA patients were recruited from the community and were randomised into an experimental and a control group. In the experimental group, the subjects were taught a set of nerve mobilization exercises while the subjects in the control group were taught a set of gentle joint mobilization exercises. Both groups were instructed to practice the exercises daily. After a 4-week period, their RA pain scale (RAPS) and pain scores were examined, as well as the C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR). Subjects in the experimental group showed improvements in RAPS and pain scores after 4 weeks of nerve mobilization exercises, while CRP and ESR values remained unaffected. These preliminary data showed that nerve mobilization exercises might be beneficial in controlling joint pain in RA patients.